2000
DOI: 10.2135/cropsci2000.4051417x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships and Fingerprinting of Rapeseed Cultivars by AFLP: Consequences for Varietal Registration

Abstract: At present, registration and protection of rapeseed (Brassica napus L.) cultivars relies on a small number of morphological traits. As the number of cultivars increases, the ability to distinguish them on the basis of these traits becomes more difficult. New descriptors like molecular markers are required to maintain the efficiency of registration testing. The objectives of this study were to (i) evaluate the discrimination power of 17 amplified fragment length polymorphism (AFLP) primer combinations tested on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 29 publications
9
105
0
5
Order By: Relevance
“…Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008). Most of the cultivars (22 out of 29) were represented by a single genetically homogeneous line, which was obtained after several generations of selfing (Table 1).…”
Section: Plant Materialssupporting
confidence: 54%
See 1 more Smart Citation
“…Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008). Most of the cultivars (22 out of 29) were represented by a single genetically homogeneous line, which was obtained after several generations of selfing (Table 1).…”
Section: Plant Materialssupporting
confidence: 54%
“…Our worldwide sample encompassed three main B. napus gene pools (ssp oleifera, ssp rapifera, and ssp pabularia), included both winter and spring oilseed types (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006), and thus represented a major part of B. napus genetic diversity. Although phenotyping other B. napus accessions could provide supplementary information, the dichotomy of meiotic behaviors found here certainly highlights the overall variation present in this species, which contains germplasm of shared recent common ancestry (Prakash and Hinata, 1980;Allender and King, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic similarity estimates can differ due to differences in the number of marker observations and in the character of polymorphic markers. Generally, the percentage of polymorphic DNA bands is smaller for AFLP and yet this technique is more efficient than RAPD and isozymes for analyzing genetic divergence, thanks to the large number of polymorphic DNA fragments per assay unit (Lombard et al, 2000;Simoniuc et al, 2002). Our study confirmed this: the RAPD method generated 61.0% polymorphic DNA fragments, and the AFLP method only 34.5% (Tabs.…”
Section: Discussionmentioning
confidence: 99%
“…L'application d'un modèle linéaire liant chaque variable phénotypique quantitative à des marqueurs moléculaires a permis d'économiser la mise au champ d'un tiers de la collection de référence, sans risque d'erreur significatif, dans une étude réalisée sur les 145 lignées de maïs présentées précédemment [5]. Pour plus de sécurité, dans les simulations réalisées par Nuel et al, seules les fausses distinctions ont été autorisées (dès qu'une lignée de référence avait une distance prédite avec la lignée candidate inférieure à la borne supérieure, elle était implantée à ses côtés).…”
Section: Gestion Des Collections De Référenceunclassified